Development of 3D super-resolution tomographic STED microscopy and its application to studies on bone resorption - Deguchi, Takahiro (Annales Universitatis Turkuensis D 1208, 2015)
In this doctoral thesis, a tomographic STED microscopy technique for 3D super-resolution imaging was developed and utilized to observebone remodeling processes. To improve upon existing methods, wehave used a tomographic approach using a commercially available stimulated emission depletion (STED) microscope. A certain region of interest (ROI) was observed at two oblique angles: one at a standard inverted configuration from below (bottom view) and another from the side (side view) via a micro-mirror positioned close to the ROI. The two viewing angles were reconstructed into a final tomogram. The technique, named as tomographic STED microscopy, was able to achieve an axial resolution of approximately 70 nm on microtubule structures in a fixed biological specimen. High resolution imaging of osteoclasts (OCs) that are actively resorbing bone was achieved by creating an optically transparent coating on a microscope coverglass that imitates a fractured bone surface. 2D super-resolution STED microscopy on the bone layer showed approximately 60 nm of lateral resolution on a resorption associated organelle allowing these structures to be imaged with super-resolution microscopy for the first time. The developed tomographic STED microscopy technique was further applied to study resorption mechanisms of OCs cultured on the bone coating. The technique revealed actin cytoskeleton with specific structures, comet-tails, some of which were facing upwards and some others were facing downwards. This, in our opinion, indicated that during bone resorption, an involvement of the actin cytoskeleton in vesicular exocytosis and endocytosis is present. The application of tomographic STED microscopy in bone biology demonstrated that 3D super-resolution techniques can provide new insights into biological 3D nano-structures that are beyond the diffraction-limit when the optical constraints of super-resolution imaging are carefully taken into account.

Tomografisen STED superresoluutio mikroskooppitekniikan kehittäminen, sekä sen sovellus luubiologian tutkimuksessa Väitöskirja käsittelee STED super-resoluutio kerroskuvausmikroskooppitekniikan kehittämistä, sekä sen sovellusta luuston uusiutumisprosessin havainnoinnissa. Tekniikka kehitettiin kaupallista STED mikroskooppia hyödyntäen. Kerroskuvausmenetelmä perustuu näytteen kuvaamiseen kahdesta eri suunnasta, alta sekä sivusta; sivunäkymä muodostettiin mikroskooppinäytteen päälle, kuvattavan kohteen yläpuolelle vinosti asetetun pienen peilin kautta, jonka jälkeen projektiot yhdistetään laskennallisesti yhdeksi kerroskuvaksi. STED kerroskuvaustekniikka mahdollisti solun sisäisten mikroputkirakenteiden havainnoinnin 70nm pitkittäisresoluutiolla. Pystyäksemme kuvaamaan luuta aktiivisesti resorpoivia osteoklastisoluja korkealla optisella erottelukyvyllä, kehitimme mikroskooppilasille muodostettavan, optisesti läpinäkyvän pinnoitteen, joka imitoi murtunutta luupintaa. Pinnoite mahdollisti osteoklastisolujen luun resorptioon liittyvien soluelinten kuvantamisen 2D STED mikroskooppia käyttäen 60 nm lateraaliresoluutiolla; tämä on ensimmäinen kerta kun kyseisiä solurakenteita on pystytty kuvaamaan super-resoluutio mikroskoopilla. Käytimme kehitettyä tomografista STED tekniikkaa osteoklastisolujen resorptiomekanismin kuvantamisessa, uutta läpinäkyvää luupinnoitetta hyväksikäyttäen. Tomografiatekniikalla muodostetuista kuvista voidaan nähdä aktiini tukirakenteiden spesifisiä rakenteita, jotka meidän mielestämme viittaavat niiden osallistumiseen vesikkeleiden endo- ja eksosytoosiin luun resorptioprosessin aikana. Tomografinen STED mikroskopia, yhdistettynä uuteen luupinnoitteeseen avaa uusia mahdollisuuksia kolmiulotteisten nanorakenteiden havainnointiin, tutkittaessa luuston uusiutumisprosessia.